Two new species of Bebearia Hemming, 1960, as further evidence of centre of endemism of butterflies in Western Nigeria (Lepidoptera: Nymphalidae: Limenitinae) - Sáfián, Szabolcs; Pyrcz, Tomasz; Brattström, Oskar (Zootaxa, 2016)
Two new endemic butterfly species from the genus Bebearia: B. oshogbo sp. nov. and B. wojtusiaki sp. nov., are described from western Nigeria; B. oshogbo is most closely related to the Guineo-Congolian B. tentyris (Hewitson) and the Upper Guinean B. osyris (Schultze), whereas B. wojtusiaki constitutes a morphological and biogeographic link between the Central African B. plistonax (Hewitson) and the Upper Guinean endemic B. arcadius (Fabricius). The finding of these new species gives further strong evidence that western Nigeria should be recognized as a distinct biogeographic sub-region of West Africa, as the area hosts a substantial number of endemic taxa (listed in the discussion).